Cambodia Trade Corridor Performance Assessment - World Bank Group (Phnom Penh, 2014)
The study found that logistics costs are high due to transshipment costs and various forms of payments. Many of these payments are imposed by the private sector with little or no transparency on how or where the costs are incurred. International trade corridors in Cambodia therefore perform well in terms of time but not cost. However, the corridors with transshipment have higher costs than the national corridor between Phnom Penh and Sihanoukville or the river corridor to the port of Cai Mep in Vietnam. Large shippers and international firms prefer to use several sub-contractors to make logistics arrangements so they do not have to coordinate what can be fairly complex and challenging arrangements for shipments. Intermediation in logistics is largely carried out by local agencies, leading to high intermediation costs. The main reason for the high intermediation cost is the prevalence and wide acceptance of facilitation fees as inducements for fast clearance and processing. Facilitation fees, largely informal, contribute to the high costs of logistics. Intermediaries, mostly forwarders and brokers, play a key role in collecting these payments. However, payment of such fees is clouded by lack of transparency. One of the main challenges is how to deal with informal payments in logistics in Cambodia. Another contributor to high costs is private sector capacity in the provision of logistics services, which is still low. Most of the truck fl eet is operated by family-run businesses owning a few trucks. Trucks are generally old which contributes also to the lack of appetite to operate across borders and at the same time compromises the feasibility of developing an effective transit system.